Range of Body Mass Index and the risk of breast cancer - Sobek, Alicja; Lorenc, Karol; Fałkowska, Urszula; Poleszak, Julita; Piecewicz-Szczęsna, Halina (Journal of Education, Health and Sport, 2018)
Introduction. Obesity leads to an increased incidence of many diseases. The research subject of scientists is the impact of obesity on breast cancer as one of the most commonly diagnosed cancers among women. Aim of the study. Analysis of the relationship between overweight and obesity with the risk of invasive breast cancer. Material and method. Review of studies on the association of obesity with the incidence of breast cancer published in the last 10 years.Results. The study conducted in 67142 women who were measured at baseline weight is noteworthy. Overweight and obese women showed an increased risk of invasive breast cancer with a positive estrogen and progesterone receptor (HR 1.86; CI 1.60-2.17). The presented analysis of 1017 cases of women suffering from breast cancer showed that the BMI above 25kg/m2 in both the period before and after menopause was associated with a larger tumor size, shorter period of disease (DFS), overall survival (OS) (P <. 001) and a higher risk of recurrence and death due to illness (P <0.05). In a study analyzing the relationship of BMI and various subtypes of breast cancer in which 657 women participated, the high BMI in postmenopausal women is most strongly associated with a more benign form of breast cancer, which immunohistochemical appearance is as follows: ER +, PR +, HER2-, Ki67low, Bcl-2 + and p53- (HR per 5 kg / m2: 1.44 [1.10 1.90], p = 0.009). Conclusions. The above analysis unequivocally convinces that the promotion of a healthy lifestyle and the development of obesity prevention programs may contribute to reducing the risk of breast cancer in women.StreszczenieWprowadzenie. Otyłość prowadzi do zwiększonej zachorowalności na wiele chorób. Przedmiotem badań naukowców jest wpływ otyłości na raka piersi. Celem pracy jest analiza związku nadwagi i otyłości (wyrażane w poziomie BMI) z ryzykiem wystąpienia inwazyjnego raka piersi.Materiał i metoda. Przegląd badan dotyczących związku otyłości z zachorowalnością na raka piersi opublikowanych ostatnich 10 latach.Wyniki. Na uwagę zasługuje badanie przeprowadzone u 67142 kobiet, u których zmierzono wyjściową masę ciała. Kobiety z nadwagą i otyłością wykazywały zwiększone ryzyko inwazyjnego raka piersi z dodatnim receptorem estrogenu i progesteronu (HR 1,86; CI 1,60-2,17). Analiza 1017 przypadków kobiet cierpiących na raka piersi wykazała, że BMI powyżej 25 kg/m2 zarówno w okresie przed menopauzą, jak i po menopauzie było związane z większym rozmiarem guza, krótszym okresem choroby (DFS), całkowitym przeżyciem (OS) ( P <0,001) i większe ryzyko nawrotów i śmierci z powodu choroby (P <0,05).W badaniu analizującym zależność BMI od różnych podtypów raka piersi, w których uczestniczyło 657 kobiet, wysoki BMI u kobiet po menopauzie jest najsilniej związany z bardziej łagodną postacią raka piersi: ER +, PR +, HER2-, Ki67low, Bcl-2 + i p53- (HR na 5 kg / m2: 1,44 [1,10 1,90], p = 0,009).Wnioski. Powyższa analiza jednoznacznie przekonuje, że promowanie zdrowego stylu życia i opracowywanie programów zapobiegania otyłości może przyczynić się do zmniejszenia ryzyka wystąpienia raka piersi u kobiet.